Corporate Governance And Company Value: An Investigation Into The Role Of ACSG Score - Chanry, Kevin; Maya, Sylviana; Siahaan, Uke Marius (Universitas Pamulang, 2023)
This study investigates the complex relationships between Good Corporate Governance (GCG) scoring, specifically the ASEAN Corporate Governance Scorecard (ACGS) score and company value. The ACGS score, a standardized measure of corporate governance, is used to assess the performance of publicly traded companies in Indonesia from 2017 to 2020. The study reveals a significant negative impact of the ACGS score on firm value, suggesting that while the ACGS score provides a standardized measure of corporate governance, it may not fully capture the nuances of individual company practices. The checkbox-based nature of the ACGS score might be seen as a mere compliance requirement rather than a true reflection of the company's corporate governance performance. However, when control variables are introduced, the effect of the ACGS score on firm value weakens and becomes insignificant. This suggests that the firm value is influenced more by financial performance compared to corporate governance performance. The study concludes that while the ACGS score can provide some insights into a company's corporate governance performance, its impact on firm value can be overshadowed by other factors. Therefore, a comprehensive approach that considers various control variables is necessary to accurately assess firm value.